THE EFFECTS OF RALOXIFENE ON BONE TURNOVER, BMD AND SERUM LIPID PROFILE IN WOMEN WITH POSTMENOPAUSAL OSTEOPOROSIS - Mehmet Fatih Uzun,; Göknur Karahan,; Canan Çelik,; Belgin Karaoğlan, (Archives of Rheumatology, 2005)
Using several pharmacological agents in osteoporosis treatment, it is possible to affect inherent pattern of disease and decrease the incidence of fractures. The aim of this study was to examine the effects of raloxifene treatment on bone turnover, bone mineral density and serum lipid profile. Total 39 healthy postmenopausal women with a bone mineral density T-score of lumbar spine or femoral neck below -2.5 were randomly assigned to two groups. 22 women received 60 mg/day raloxifene, 1200 mg/day calcium and 800 iu/day cholecalciferol, 17 women received only 1200 mg/day calcium and 800 iu/day cholecalciferol. Subjects were treated for 1 year. Biochemical marker of bone turnover and serum lipids were measured at baseline, third month and first year. Bone mineral density was measured at baseline and first year. There was no significant difference in baseline characterictics between two groups. The mean values of lumbar BMD were increased by first year in both groups (% 7,638 and % 2,403 respectively). The increment was significant in treatment group (p<0,001), but it was not in control group (p>0,05). There was also a significant dfference between two groups (p<0,05). However there were no significant changes in femoral neck and total hip BMD in both groups (p>0,05). The mean values of urinary N-telopeptides were significantly decreased by third month and by first year. The difference between mean changes by third month and first year of two groups was also significant (p<0,001). Urinary calcium excretion for 24 hours was decreased by third month and first year in treatment group, but not significant (p>0,05). In control group, urinary calcium excretion for 24 hours was increased by third month and first year. During the study; there were no statisticaly significant changes in cholesterol and LDL levels in both groups compared with baseline (p>0,05). Triglyseride levels were significantly increased by first year in both groups (p<0,05), but these changes were not significant comparing with each other (p>0,05). By first year, serum HDL level was significantly increased in raloxifene group compared with baseline (p<0,05), but this increment was not significant comparing with control group (p>0,05). This study demonstrates the favorable effects of raloxifene on lumbar spine bone mineral density and bone turnover in women with postmenopausal osteoporosis.